Higher-capacity lithium ion battery chemistries for improved residential energy storage with micro-cogeneration - Darcovich, K. (2013)
Combined heat and power on a residential scale, also known as micro-cogeneration, is currently gaining traction as an energy savings practice. The configuration of micro-cogeneration systems is highly variable, as local climate, energy supply, energy market and the feasibility of including renewable type components such as wind turbines or photovoltaic panels are all factors. Large-scale lithium ion batteries for electrical storage in this context can provide cost savings, operational flexibility, and reduced stress on the distribution grid as well as a degree of contingency for installations relying upon unsteady renewables. Concurrently, significant advances in component materials used to make lithium ion cells offer performance improvements in terms of power output, energy capacity, robustness and longevity, thereby enhancing their prospective utility in residential micro-cogeneration installations. The present study evaluates annual residential energy use for a typical Canadian home connected to the electrical grid, equipped with a micro-cogeneration system consisting of a Stirling engine for supplying heat and power, coupled with a nominal 2 kW/6 kW h lithium ion battery. Two novel battery cathode chemistries, one a new Li–NCA material, the other a high voltage Ni-doped lithium manganate, are compared in the residential micro-cogeneration context with a system equipped with the presently conventional LiMn2O4 spinel-type battery.